PENGEMBANGAN MODEL PARENTING BERBASIS E-MODUL UNTUK ANAK - Resfa Ati (COLLASE (Creative of Learning Students Elementary Education), 2023)
The objectives of this study are: (1) to analyze the need for an e-module-based parenting model for children's independence (2) to formulate a design for developing an e-module-based parenting model (3). The type of research is Research and Development (R&D) from Sugiyono. adopting the theory of Borg and Gall, the research simply uses ten steps (1) Research and information gathering, (2) Designing a product, (3) Developing a prototype (preliminary), (4) Preliminary testing in the field, (5) Revision of the main product, (6) Main product trial, (7) Product use revision, (8) Field use trial, (9) Final product revision, (10) Dissemination and implementation. Sources of data are parents and teachers at basic level formal education institutions in Bangsri, Bangsri Jepara District. Data collection techniques in the form of interviews, observations, questionnaires, documentation. The research instrument is a structured interview guide for teachers, validation questionnaires for material experts. The results of the study: 1) The results of the needs analysis show that parents need interesting modules for reference materials and teaching materials in the implementation of parenting in order to make children independent based on the results of interviews and observations. 2) Development of parenting media in the form of e-module-based parenting models and e-module usage manuals; 3) The feasibility of the e-module-based parenting module based on the validation results from media experts is 91, material expert validation is 87 and linguist validation is 93. The validation criteria from the three validators are very valid and very feasible to use in parenting activities for elementary level children. The conclusion of the study is that the development of an e-module-based parenting model is very suitable to be used to improve parents' skills in making children independent at the elementary school level. Keywords: e-module, Parenting, elementary school age children